PENGARUH METODE LATIHAN BERBANTUAN MEDIA AUDIO TERHADAP KETERAMPILAN BERBICARA SISWA KELAS III SDN 24 - Agustina, Tia; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis reseatch aims to analyze the effect of drill method audio media aided toward third-grade studentsâ€™ speaking skill of class III Students of Pontianak City 24 Elementary School. The method is used in this research is experiment mothod, the form of the research is quasi experimental design with nonequivalent control group design. The population and sample in this research is all third-grade students of Pontianak City 24 Elementary School. The tools of data collection is one essay test. Based on the data analysis,the post test average in experiment class is 66,67 but in control class is 58,34. The result of t-test is 1,824 and t-table Î± = 5% (with dk = 25+24-2=46) is 1,667 which means t-count (1,824) > t-table (1,667), then the alternative hypothesis is accepted. The effect size is 0.4645 (medium criteria). This can be concluded that drill method gives the good effect toword studentsâ€™ mathematics representative skill of class III Students of Pontianak City 24 Elementary School.Â Keywords: Practice method, Audio Media, Speaking Skill.